2018
DOI: 10.1016/j.bone.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Bone microarchitecture, biomechanical properties, and advanced glycation end-products in the proximal femur of adults with type 2 diabetes

Abstract: Skeletal fragility is a major complication of type 2 diabetes mellitus (T2D), but there is a poor understanding of mechanisms underlying T2D skeletal fragility. The increased fracture risk has been suggested to result from deteriorated bone microarchitecture or poor bone quality due to accumulation of advanced glycation end-products (AGEs). We conducted a clinical study to determine whether: 1) bone microarchitecture, AGEs, and bone biomechanical properties are altered in T2D bone, 2) bone AGEs are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 48 publications
(58 reference statements)
10
101
1
1
Order By: Relevance
“…These results confirm increased accumulation of the AGE pentosidine and sugars bound to the collagen matrix in cancellous tissue from men with T2DM and are consistent with other reports of bone tissue pentosidine in men and women with and without T2DM . Total fAGE concentration in this study was not different between groups, consistent with another report of tissue fAGEs in proximal femoral cancellous bone in men and women with and without T2DM . In vitro glycosylation/ribosylation studies of human cancellous bone offer the ability to isolate the effects of AGE accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results confirm increased accumulation of the AGE pentosidine and sugars bound to the collagen matrix in cancellous tissue from men with T2DM and are consistent with other reports of bone tissue pentosidine in men and women with and without T2DM . Total fAGE concentration in this study was not different between groups, consistent with another report of tissue fAGEs in proximal femoral cancellous bone in men and women with and without T2DM . In vitro glycosylation/ribosylation studies of human cancellous bone offer the ability to isolate the effects of AGE accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, it is important to note that both cancellous and cortical bone contribute to structural performance at the whole‐bone level, and cortical bone is more critical for load‐bearing in the hip . In the first study relating bone tissue AGES to mechanical properties from tissue from patients with T2DM, Karim and colleagues reported a trend toward greater AGEs in the cortex of the femoral neck (+ 19%, P = 0.09) and greater creep indentation distance (+ 18%) and indentation distance increase (+ 20%) in cortical bone from patients with T2DM versus non‐DM controls; however, no relationships between bone AGEs and the indentation variables were observed . These results highlight the complexity of assessing the relationships between AGEs and bone fragility across levels of structural hierarchy and suggest an important area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the group size of 31 to 34 in this study is tiny by the standards of large epidemiologic cohorts, it significantly exceeds the standard in a field where conclusions about human bone quality sometimes rely on a handful of specimens. The robust analyses of human bone quality and composition join published studies by Pritchard and colleagues and Karim and colleagues in advancing our understanding of the mechanisms of bone fragility in human diabetes. The results challenge the assumptions based on animal models.…”
Section: Commentarymentioning
confidence: 83%
“…In fact, studies have reported that patients with T2DM have normal to high BMD by DEXA . Recent studies have found that the trabecular microarchitecture and mechanical properties of cancellous bone of T2DM (measured by cyclic reference point indentation and unconfined compression) are indistinguishable from osteoarthritic (OA) controls, whereas the apparent stiffness and yield strength were increased in cancellous cores from the femoral neck of patients with T2DM (and osteoarthritis) compared with OA controls . Impaired mechanical properties (decreased strength, stiffness, and toughness) have been reported for hyperglycemic mouse femurs tested in bending .…”
Section: Introductionmentioning
confidence: 99%